Commercialisation of customised pharmaceutical compounded creams and ointments in a community pharmacy setting - Matulodi, Itumeleng Bianca (University of the Witwatersrand, Johannesburg, 2023)
This research intended to discover and explore a business opportunity for high-quality, cost-effective creams/ointments and the therapeutic benefits to the end-user in a community pharmacy setting. A mixed research method was utilised in the proposed business venture in the form of primary and secondary data collection, solidifying methods in answering the research questions. A random sample size of 120 adults was used for the quantitative survey questions and 80 adults for the qualitative survey. Microsoft Excel spreadsheet was utilised to enter all the data and to make inferences from the primary and secondary data obtained. The Statistical Packages for Social Sciences (SPSS) version 28 was used to code data and run the statistical analysis. The research results revealed that the cream combination may be prescribed by either the GP/Specialist and will not depend on gender, age, the frequency of prescribing, and whether the individual is using it for the first time or more. There was a perfect association between price and cream. Pharmaceutical compounded creams/ointments have a critical part in providing patient- centric products and services for individuals who may be underserved. This is a business that can be leveraged.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Customised creams/ointments; Pharmaceutical compounding; Patient-centric; Value-driven; UCTD; SDG-3: Good health and well-being